Análisis patológico y estructural de los bloques de vivienda fiscal de la Armada del Ecuador ubicados en Abel Gilbert 1 Durán tomando como muestra los bloques No 23 y No 24 - Plúas Moran, Marcos Joffre (2025)
The present thesis of the pathological and structural analysis of the public housing blocks of the Ecuadorian Navy located in Abel Gilbert 1 Durán, taking blocks No. 23 and No. 24 as a sample, It is a study of damages, defects and future structural problems, taking as reference two housing blocks since the same problems are repeated in all blocks. This study tries to compare the pathological problems of buildings from the same climatic zone, from other countries such as México, Perú and Colombia. In these countries, pathology studies of their buildings are carried out, conferences and workshops are held on how the study should be carried out. of each defect or damage to the structure of each building..........